Four discourses and sinthomatique writing in Saul Bellow’s Herzog: a Lacanian approach - Teymouri, Tohid; Ladani, Zahra Jannessari; Abbasi, Pyeaam (Penerbit Universiti Kebangsaan Malaysia, 2018)
This paper studies sinthomatique writing in Saul Bellow’s Herzog in the form of letter-writing. Referring to Lacanian theory, the Sinthome is discussed in the study as a system of signification that exploits the unconscious digging for jouissance. Connected to jouissance in writing unconscious, the Sinthome is the fourth ring in the Borromean knot that protects a subject against psychosis by intersecting the Imaginary, the Symbolic, and the Real orders. This study further develops the idea of the Sinthome in relation to the Four Lacanian Discourses. In respect to Discourses of the Master, University, Hysteric, and Analyst, the following procedure is introduced for a subject excluded spatially and socially: foreclosure of master signifier, rejection of desire, reception of jouissance, and communication of the unconscious. The subject in above-mentioned moves needs a sinthome to protect his/her subjectivity against disintegration. Regarding Jacques Lacan’s example about James Joyce in using specific styles and epiphany, letter-writing is introduced as the Sinthome in Herzog that helps Herzog deliver his subjectivity from dissolution. Herzog is a character on the verge of breakdown and madness after his second divorce. He reconfigures his subjectivity when he forecloses AMERICA as master signifier, no longer enjoys knowledge, receives contradictions and truth, and ultimately jots down his unconscious. Finally, the role of the Sinthome is explored in the production of art. The Sinthome is considered as a kind of unique discourse through which a psychotic artist is enabled to originate new artistic productions.